Developing Local Wisdom-Based Teaching Materials on "Family Addressing Terms" for Elementary School Students: Validation Analysis Using the 4D Model - Guslinda Guslinda; Otang Kurniaman; Liong Nyuk Firdaus; Hadriana Hadriana (Ignatianum University Press, 2024)
Objectives of the research: The utilization of media in teaching materials serves to impart knowledge of local wisdom by incorporating visuals tailored to students' characteristics. Local wisdom as part of national identity should be recognized by the next generation through learning. Each culture in every region possesses unique characteristics that distinguish it from others. Hence, appropriate teaching materials on local wisdom should be developed for elementary school students. This study aims to design teaching materials focusing on addressing terms used in several regions in Riau. Research methods: Employing a Research and Development (R&D) approach, this study follows the 4D model, which consists of defining, designing, developing, and disseminating phases. A short description of the context of the issue: This article underscores the importance of developing local wisdom-based teaching materials for elementary school students. It emphasizes the need for elementary school materials aligning with the local wisdom that are relevant to the local community and facilitate students' understanding and appreciation of their culture. In today's digital millennium, many elementary school students lack awareness or appreciation of local wisdom, including familial terms of address. Research findings: In addition, experts in teaching materials, media, and linguistics analyzed the data using descriptive percentage-based methods to validate the findings. Experts evaluated four key aspects: content, language, presentation, and appropriateness. Results indicated high feasibility, with content scoring 95%, language 96.87%, presentation 97.5%, and graphics 93.75%, culminating in an overall average score of 95.78% in the "very feasible" category. These findings suggest potential for broader application and study. Conclusions and recommendations: The development and testing of local wisdom teaching materials for elementary school students have demonstrated their suitability for use. Based on the validation results by experts in teaching, media, and language, the materials are highly feasible, so, further exploration and dissemination of these materials on a larger scale are recommended.